2008
DOI: 10.1167/iovs.07-0389
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Therapy for Corneal Neovascularization Using Polymeric Micelles Encapsulating Dendrimer Porphyrins

Abstract: PDT with DP-micelle and free DP can provide efficacious treatment of corneal neovascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 24 publications
1
21
0
1
Order By: Relevance
“…By now, most of these nanostrategies are used in many areas of PDT. For example, dendrimer porphyrin encapsulation into polymeric micelles [58] is used for the treatment of corneal neovascularization, a major sight-threatening condition caused by inflammation, infections and degenerative disorders [69,70,71]. Visudyne ® the first photodynamic drug approved for treatment of age related macular degeneration (AMD) is used to reduce the risk of vision loss.…”
Section: 'Nano' Strategies For Photosensitizermentioning
confidence: 99%
“…By now, most of these nanostrategies are used in many areas of PDT. For example, dendrimer porphyrin encapsulation into polymeric micelles [58] is used for the treatment of corneal neovascularization, a major sight-threatening condition caused by inflammation, infections and degenerative disorders [69,70,71]. Visudyne ® the first photodynamic drug approved for treatment of age related macular degeneration (AMD) is used to reduce the risk of vision loss.…”
Section: 'Nano' Strategies For Photosensitizermentioning
confidence: 99%
“…The use of antisense oligonucleotides has already moved into a Phase II clinical trial with studies of gene signal (GS)-101, an antisense oligonucleotide that inhibits the expression of IRS-1 and is designed only to target currently growing neovessels. In this randomized, double-blind, multicenter, dosedetermining study, four groups of 10 patients were treated with three doses of GS-101 (43,86, and 172 mg/day total) or placebo administered twice daily in eye drops. The results showed that GS-101 eye drops were well tolerated at an optimal dose of 86mg/day, which specifically inhibited and promoted the regression of NV, providing an effective and noninvasive approach for the treatment of active corneal angiogenesis.…”
Section: Anti-vegf Treatmentsmentioning
confidence: 99%
“…MRI) [56]. Thus, they can be used for oral, transdermal, ocular and intravenous deliveries [60,61]. Moreover, dendrimers have shown that they can easily cross cell barriers by both paracellular and transcellular pathways [56].…”
Section: Dendrimersmentioning
confidence: 99%